Neonatal lupus in an infant with maternal history of Jessner’s lymphocytic infiltrate - Katakam, Bhumesh Kumar; Dhabal, Arunima; Gurram, Narsimha Rao Netha; Chintagunta, Sudharani (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Neonatal lupus erythematosus (NLE) is a rare autoimmune condition occurring in infants born to mothers with circulating antinuclear autoantibodies, particularly anti-Ro and anti-La. It presents with a characteristic cutaneous rash, which may be accompanied by systemic manifestations. The condition is mostly self-limited, although congenital heart block, if present, is irreversible. We report a rare case of cutaneous NLE in an infant of a mother with a prior history of Jessner’s lymphocytic infiltration of skin (JLIS), which is arguably a variant of cutaneous lupus erythematosus (LE). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. This report concerns an infant presenting with cutaneous manifestations of NLE, without any systemic involvement. The mother was asymptomatic, but had been previously diagnosed with JLIS. The diagnosis of NLE was made based on serological results from both the infantile and maternal blood. Conservative management was sufficient to achieve complete resolution. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The case underscores the importance of considering NLE in infants presenting with annular rash, even in asymptomatic mothers with no known rheumatic disease. It also suggests that JLIS may belong to the same spectrum as LE, rather than being a separate entity. This warrants careful prenatal monitoring in mothers with a concurrent or prior diagnosis of JLIS.